An exploratory analysis of quality of working life in the banking sector - Mara Regina dos Santos Barcelos; André Luís Policani Freitas (Brazilian Journal of Operations & Production Management, 2014)
Nowadays Quality of Working Life (QWL) has been considered an additional advantage since satisfied employees can produce more and better, and consequently they can improve the profitability of the companies. In this context, this paper presents an exploratory analysis of QWL in the banking sector, which was conducted in a municipality of the state of Rio de Janeiro, Brazil. A hybrid QWL evaluation model was used based on existing models and scientific studies in the literature, incorporating current characteristics of the banking sector. Cronbach’s alpha and item-to-total correlations analysis were conducted in order to measure the reliability of the questionnaire.Mann-Whitney U test was conducted in order to examine the differences in QWL according to perception of male and female workers, and Quartile analysis was used to identify the most critical issues. As a result, special attention should be dedicated to the critical questions, but also considering some questions on which there is a difference in the workers’ perception of QWL concerning gender.